2009
DOI: 10.1098/rsif.2009.0067
|View full text |Cite
|
Sign up to set email alerts
|

Towards a quantitative understanding of the within-host dynamics of influenza A infections

Abstract: Although the influenza A virus has been extensively studied, a quantitative understanding of the infection dynamics is still lacking. To make progress in this direction, we designed several mathematical models and compared them with data from influenza A infections of mice. We find that the immune response (IR) plays an important part in the infection dynamics. Both an innate and an adaptive IR are required to provide adequate explanation of the data. In contrast, regrowth of epithelial cells did not seem to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
199
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(202 citation statements)
references
References 64 publications
3
199
0
Order By: Relevance
“…We proceed by first presenting mathematical models previously proposed to describe the within-host dynamics of influenza [28] and pneumococcal [29] infections in isolation. Each model attempts to capture the kinetics of pathogen proliferation, the resultant immune response and its impact on pathogen load during the course of an infection.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We proceed by first presenting mathematical models previously proposed to describe the within-host dynamics of influenza [28] and pneumococcal [29] infections in isolation. Each model attempts to capture the kinetics of pathogen proliferation, the resultant immune response and its impact on pathogen load during the course of an infection.…”
Section: Methodsmentioning
confidence: 99%
“…The mathematical equations describing the system and the parameter estimates are presented in the electronic supplementary material, equations S1 and table S1, respectively. Handel et al [28] parametrized the within-host influenza model by statistical fitting to data from two separate experimental studies: (i) the study by Kris et al [33], which observed viral loads in both wild-type (normal) and nude, athymic (no antibody response) mice during an H3N2 infection, and (ii) the study by Iwasaki & Nozima [34], which documented viral loads, IFN and antibody levels, as well as lung lesions in mice with H1N1 infection under various permutations of treatments. We illustrate representative viral titres and different measures of immune response over the course of the infection, as predicted by the model, in the electronic supplementary material, figures S1 and S2.…”
Section: The Influenza Modelmentioning
confidence: 99%
See 3 more Smart Citations